Integrating Behavior in Life-History Theory: Allocation versus Acquisition?. (February 2021) - Laskowski, Kate L.; Moiron, Maria; Niemelä, Petri T.
Abstract : Central theories explaining the maintenance of individual differences in behavior build on the assumption that behavior mediates life-history trade-offs between current and future reproduction. However, current empirical evidence does not robustly support this assumption. This mismatch might be because current theory is not clear about the role of behavior in individual allocation versus acquisition of resources, hindering empirical testing. The relative importance of allocation compared to acquisition is a key feature of classic life-history theory, but appears to have been lost in translation in recent developments of life-history theory involving behavior. We argue that determining the relative balance between variation in resource allocation and acquisition, and the role of behavior in this process, will help to build more robust and precise predictions. Highlights: Current theory predicts that among-individual variation in behavior is maintained by variation in how individuals resolve life-history trade-offs. Individuals that exhibit 'fast' phenotypes are expected to allocate more into current reproduction and acquire more resources to fuel this investment, whereas 'slow' phenotypes, that have lower acquisition, are predicted to allocate more into future reproduction. Thus, current theory assumes the simultaneous presence of behaviorally mediated among-individual variation in both resource allocation and resource acquisition. We highlight how explicit considerations of whether behavior is more closely linked to variance in resource acquisition or resource allocation can improve predictions about the observed correlations between behavior and life-history traits, and draw general implications for life-history theory.